2016
DOI: 10.1177/1557988315604019
|View full text |Cite
|
Sign up to set email alerts
|

The Ebb and Flow of Filipino First-Time Fatherhood Transition Space

Abstract: Fatherhood, as a developmental process, is both a human experience and a text that needs to be read. For developing nations like the Philippines, little is known about the process undergone by first-time fathers on their transition to fatherhood, and how nurses can play a significant role in assisting them. This grounded theory study purported to conceptualize the multifaceted process of transition from the lens of Filipino first-time fathers' lived experiences. A total of 20 first-time fathers from Metro Mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Furthermore, it is important to consider the role of the timing of the interviews in the interpretation of the findings. Other researchers have shown that most fathers interviewed a short time (a few weeks) following the birth of their first child described this event as being very special regardless of whether they were present at the birth (Miller, 2011; Villamor et al, 2016). Our interviews did not include such descriptions, most probably since we did not ask directly about the men’s experiences concerning childbirth itself and, moreover, because of this event having taken place more than 1½ years previously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is important to consider the role of the timing of the interviews in the interpretation of the findings. Other researchers have shown that most fathers interviewed a short time (a few weeks) following the birth of their first child described this event as being very special regardless of whether they were present at the birth (Miller, 2011; Villamor et al, 2016). Our interviews did not include such descriptions, most probably since we did not ask directly about the men’s experiences concerning childbirth itself and, moreover, because of this event having taken place more than 1½ years previously.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to women with children, whose maternal identity is socially recognized by default, men must actively claim the father identity, as described by Miller (2011). There are clearly huge differences in terms of the process of forming the paternal identity according to the cultural context and the relationship between the fatherhood construct and masculinity as viewed in different societies and even subgroups (Hobson, 2002; Iwata, 2014; Madhavan & Roy, 2012; Roy, 2006; Villamor et al, 2016; Wei-Jun, 2013). Such differences can be explained via the prevailing sharp distinction between male and female gender roles and the extent to which they interrelate and/or overlap.…”
Section: Involved Fatherhood and Changing Masculine Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reinforces that the behavioral, emotional, physical and social changes experienced by men in response to their partner's pregnancy signal the understanding of their responsibility and an early commitment to the well-being of their families [38][39][40][41] . The family support network, the partner and friends, as providers of emotional, informative and tangible support 41,42 , therefore become crucial in facilitating this transitional process 43 .…”
Section: Discussionmentioning
confidence: 99%
“…This period was also examined in this study, with the difference that the focus was not on pregnancy events but on male stories and what underlies their stories. Villamor et al (2016) showed that the B.R.I.D.G.E., a theoretical approach, also shows the different stages men go through during the transition to fatherhood. Three stages are identified: pregnancy, childbirth, and several weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%